Pengaruh Kualitas Produk Terhadap Keputusan Pembelian Produk Motor Honda CBR 150CC pada PT. Tunas Dwipa Matra Cabang Kota Jambi - Adek Hariyanto (Science of Management and Students Research Journal (SMS), 2020)
This study was intended to know the effect of product quality on purchasing decisison of Motorcycle of Honda CBR 150cc at PT Tunas Dwipa Matra Kota Jambi. Based on the data obtained from this study, the sale of motorcycle of  Honda CBR 150cc at PT Tunas Dwipa Matra Jambi has fluctuated during the period 2014 to 2018. the sale of motorcycle of  Honda CBR 150cc at PT Tunas Dwipa Matra Jambi has decrease in 2017. The retrieval method by random sampling, data collection is done by questionnaires and interviews, the analysis used is simple linear regression analysis, correlation coefficient of determination, classic asumtion test and stastical test t.PT Tunas DwipaMatra Jambi established in Jambi since 2010 that sells various type of Honda Motorcyle. Product Quality have a positive an significant effect on purchasing decisions with a regression coefficient of 0.333. this is evidenced by the results of the  t-test analysis which shows the value of t-count 3,691>t-tablle value  2.021 and the significance level of 0.001 < 0.05 significance probability   and has no classic asumtion problem. Product Quality and Purchase Decission of Motorcycle of  Honda CBR 150cc at PT Tunas DwipaMatra Jambi is good and also product quality effecting the purchasing decision of motorcycle Honda CBR 150cc at PT. Tunas Dwipa Matra kota Jambi.